Emotions at work and mental health: emerging directions - Devdutt, Janhavi; Mehrotra, Seema (International Journal Of Community Medicine And Public Health, 2018)
The present paper aims to present a brief overview of research on emotions at the workplace, and its relevance for mental health. Studies have been carried out linking emotions at work to various indices of well-being at work as well as to multiple health outcomes. The scope and utility of research focusing on day-to-day affective experiences is highlighted through studies using affective events theory as a guiding framework. There is a relative dearth of studies on emotion regulation processes at work, specifically on interpersonal regulation of emotions in work life as well as on regulation of positive emotions. Despite a boom in research on the magnitude of mental health issues at workplace and its wide-ranging implications, there is insufficient integration of research on emotions and mental health at work, with these two related strands of research evolving rather independently of each other. The overview points out areas of future research as well as implications for practice.